Pengaruh Harga, Produk dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Toko Buku Gramedia Pandanaran Semarang - Deddy Setiawan; Sri Suryoko; Sari Listyorini (Jurnal Ilmu Administrasi Bisnis, 2015)
The purpose of this study was to determine the effect of price , product and service quality to customer satisfaction Gramedia bookstore Pandanaran Semarang . The sample in this study amounted to 100 respondents using purposive sampling method. Linear regression analysis and significance test is used to prove the hypothesis using SPSS 16. Results of this study concluded that the positive effect on the price to customer satisfaction ( 27.1 percent ) . Product positive effect on customer satisfaction (30,1 percent ). Service quality has positive influence on customer satisfaction ( 18 percent ) . Price , Product and Service Quality influence on customer satisfaction ( t > t table ) . Suggestions for implementing pricing strategies through discount or exhibition event , adding the characteristics and diversity of products and improve service to customers .